In Vitro Differentiation of Human Placenta-Derived Multipotent Cells into Schwann-Like Cells - Chung-Hau Juan; Mei-Hsiu Chen; Feng-Hui Lin; Chih-Shung Wong; Chih-Cheng Chien; Ming-Hong Chen (Biomolecules, 2020)
Human placenta-derived multipotent stem cells (PDMCs) resembling embryonic stem cells can differentiate into three germ layer cells, including ectodermal lineage cells, such as neurons, astrocytes, and oligodendrocytes. The favorable characteristics of noninvasive cell harvesting include fewer ethical, religious, and legal considerations as well as accessible and limitless supply. Thus, PDMCs are attractive for cell-based therapy. The Schwann cell (SC) is the most common cell type used for tissue engineering such as nerve regeneration. However, the differentiation potential of human PDMCs into SCs has not been demonstrated until now. In this study, we evaluated the potential of PDMCs to differentiate into SC-like cells in a differentiation medium. After induction, PDMCs not only exhibited typical SC spindle-shaped morphology but also expressed SC markers, including S100, GFAP, p75, MBP, and Sox 10, as revealed by immunocytochemistry. Moreover, a reverse transcription-quantitative polymerase chain reaction analysis revealed the elevated gene expression of S100, GFAP, p75, MBP, Sox-10, and Krox-20 after SC induction. A neuroblastoma cell line, SH-SY5Y, was cultured in the conditioned medium (CM) collected from PDMC-differentiated SCs. The growth rate of the SH-SY5Y increased in the CM, indicating the function of PDMC-induced SCs. In conclusion, human PDMCs can be differentiated into SC-like cells and thus are an attractive alternative to SCs for cell-based therapy in the future.